(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
To meet the requirements of rapid measurement of oil and gas methane isotopes in offshore logging platforms, a methane carbon isotope measurement system based on mid-infrared TDLAS technology was proposed in this paper. The measuring system adopted a mid-infrared compact-linear optical structure, including an interband cascade laser (central wavelength at 2963.25 cm-1), long optical path multi-pass cell (effective optical path is 24 m) and mercury cadmium telluride detector (response wavelength is from 2 μm to 5 μm). Combining two 13CH4/12CH4 absorption lines, 2963.25 cm-1 and 2963.34 cm-1, with a high precision temperature control system using an integral separation PID control method, a temperature fluctuation within 100 mK can be achieved. In the experiment, CH4 gases with five different concentrations were configured to calibrate the measurement system, and the response linearity was more than 99%. When the integration time is 121s, the precision of isotope measurement was as low as 0.83 ‰. The average isotopic abundance of methane gas measured by the system was -10.2 ‰, and the error fluctuation was about ±0.5 ‰. It was verified that the system can rapidly measure oil and gas methane isotopes.